2012
DOI: 10.1074/jbc.m112.355032
|View full text |Cite
|
Sign up to set email alerts
|

The Antibodies against the Computationally Designed Mimic of the Glycoprotein Hormone Receptor Transmembrane Domain Provide Insights into Receptor Activation and Suppress the Constitutively Activated Receptor Mutants

Abstract: Background:The mechanism of glycoprotein hormone receptor activation is not clearly understood. Results: Antibodies against computationally designed TMD mimic bind TSHR/LHR/FSHR and inhibit hormone-independent and -dependent receptor activation without affecting respective hormone binding. Conclusion: Conformational alterations in transmembrane helices leading to receptor activation are dependent on changes in hinge-exoloop engagements. Significance: Antibodies against novel TMD mimic have therapeutic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Circular dichroism (CD) spectra of glc-derived PAS and gal-derived PAS samples using experiment (A) in comparison to calculated CD analysis of 100 ps MD simulation of glc- and gal-PAS 10-mer structures from DichroCal. Both spectra depict features indicative of helical conformations in both glc- and gal-PAS structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circular dichroism (CD) spectra of glc-derived PAS and gal-derived PAS samples using experiment (A) in comparison to calculated CD analysis of 100 ps MD simulation of glc- and gal-PAS 10-mer structures from DichroCal. Both spectra depict features indicative of helical conformations in both glc- and gal-PAS structures.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we computed CD spectra using glc- and gal-PAS polymer conformations derived from 100 ps of MD simulations with the Dichro-Cal software program to determine whether the newly developed AA models reliably represented the glc- and gal-PAS systems (Figure B). In agreement with our experimental data, the calculated spectra showed strong CD signals with a positive peak around 198 nm (compared to the 191 nm in experiment) and a negative peak at 220 nm (compared to the 219 nm in experiment).…”
Section: Resultsmentioning
confidence: 99%
“…Monoclonal antibodies directed at TSHR have been studied as antagonists of TSHR activation by TSHRbinding agonists [17][18][19]. Blocking antibodies inhibit activation of TSHR by blocking the binding of GO-Igs to the extracellular domain of TSHR.…”
Section: Tshr-targeted Treatmentsmentioning
confidence: 99%
“…Based on this structure, it was suggested that FSH binds to FSHR like "hands clasped" on the concave surface of the FSHR (9). However, this model did not include the hinge region, which is considered to play critical roles in receptor activation based on various biochemical studies (10)(11)(12). More recent studies strongly suggest unliganded ECD acts as a tethered inverse agonist imposing an inhibitory effect through the hinge region, which is converted to a stimulatory response upon ligand binding (13).…”
mentioning
confidence: 99%
“…Studies by site-directed mutagenesis, chimeric receptors, and naturally occurring mutations have demonstrated the critical role of extracellular loops and intracellular loops in FSHR function (6,12,17,18). They play key roles in ligand binding, cell surface receptor trafficking, signaling, and interaction with adaptor proteins (6).…”
mentioning
confidence: 99%